HUMAS DALAM PENGUATAN MUTU LULUSAN MELALUI DUNIA USAHA DAN DUNIA INDUSTRI (DU/DI) DI SMK NEGERI 1 PONOROGO - Arifah Nur 'Aini (Program Studi Manajemen Pendidikan Islam, 2024)
Vocational High Schools (SMK) are educational unit level institutions whose role is to create quality and potential Human Resources (HR) in their fields. Vocational High School (SMK) is a form of formal education unit that provides vocational education at secondary education level as a continuation of SMP, MTs, or other equivalent forms. Schools at educational levels and vocational types can be called Vocational High Schools (SMK) or Vocational Madrasah Aliyah (MAK), or other equivalent forms. In order to realize this law, it is necessary to have a cooperative effort that optimally involves the community and the school environment to help improve the quality of education. Therefore, there is a need for management, which is important in schools, namely management of public relations with the school (public relations), because schools are in the midst of society and are always in contact to establish cooperation so that it benefits both parties. This research discusses the role of public relations in building a partnership with DUDI to improve the competency of accounting graduates at SMK Negeri 1 Ponorogo. This research method is descriptive qualitative which is carried out using interviews and documentation. This research found that in its stages, public relations built relationships with the DUDI partnership starting with planning in the form of determining the location of street vendors and creating SOPs. Then the implementation is carried out by collecting data on the location of the PKL, archiving the MoU, and determining the PKL supervising teacher. Lastly is the evaluation which is carried out through monthly and annual meetings.